Descriptive study of 271 traumatized patients treated in the Emergency Department of the Hospital de Clínicas - Cepellini, Raúl; Henderson, Eduardo; Bañales, Cecilia; Caraballo, Mónica; Terra, Daniel; Suárez, Ruben; Gómez, Juan Carlos; Díaz, Francisco; Cassinelli, Jorge; Genta, Fernando; Müller, Augusto (Cirugía del Uruguay, 1997)
A retrospective descriptive study is carried out by analysing 271 cases of trauma of any kind admitted to the Emergency Department at the Hospital de Clínicas between May 1995 and September 1996. Authors analyse epidemiology, paraclinic, treatments, complications and mortality This study can be used as hypotheses far future research.